Perceived autonomy support, psychological needs satisfaction, depressive symptoms and apathy in French hospitalized older people. (July 2016) - Souesme, Guillaume; Martinent, Guillaume; Ferrand, Claude
Highlights: Identification of three needs satisfaction profiles. High level of psychological needs satisfaction is associated with low levels of depressive symptoms and apathy. Higher level of perceived autonomy support is associated with high levels of psychological needs satisfaction. Both competence and relatedness needs significantly and negatively explained 28% and 44% of the variance of depressive symptoms and apathy scores. Abstract: Based on the self-determination theory, the aim of the present study was (1) to provide a better understanding of older people's psychological needs satisfaction in geriatric care units, then to link this information with depressive symptoms and apathy; (2) to examine whether the perceived autonomy support from health care professionals differs between needs satisfaction profiles; and (3) to investigate for all participants how each need satisfaction was related to depressive symptoms and apathy. Participants ( N = 100; M age = 83.33 years, SD = 7.78, 61% female) completed the measures of psychological needs satisfaction, perceived autonomy support, geriatric depression and apathy. Sociodemographic data were also collected. Cluster analyses showed three distinct profiles: one profile with low-moderate need satisfaction, one profile with high-moderate need satisfaction and one profile with high need satisfaction. These profiles are distinct, and did not differ in terms of participants' characteristics, except gender. Multivariate analysis of covariance (MANCOVA) revealed that participants with low-moderate need satisfaction profile have significantly higher level of depressive symptoms and apathy, and lower levels of perceived autonomy support than participants of the two other profiles. Moreover, for all participants, regression analyses revealed that both competence and relatedness needs satisfaction significantly and negatively explained 28% of the variance in depressive symptoms score and 44% of the variance in apathy score. Our results highlight the interest to examine more thoroughly the variables fostering autonomy-supportive environment in geriatric care units, and to deepen the relationship between competence and relatedness needs satisfaction and depressive symptoms and apathy.